2010
DOI: 10.1080/00140139.2010.513746
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical differences between expert and novice workers in a manual material handling task

Abstract: The objective was to verify whether the methods were safer and more efficient when used by expert handlers than by novice handlers. Altogether, 15 expert and 15 novice handlers were recruited. Their task was to transfer four boxes from a conveyor to a hand trolley. Different characteristics of the load and lifting heights were modified to achieve a larger variety of methods by the participants. The results show that the net moments at the L5/S1 joint were not significantly different (p > 0.05) for the two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 49 publications
2
32
0
1
Order By: Relevance
“…pickup or delivery tasks preceded and followed by cyclic steps). Foot placements have been identified as a critical component to accurate biomechanical evaluation of postures adopted during lifting (Authier, Lortie, and Gagnon 1996;Bendix and Eid 1983;Plamondon et al 2006;Wickel and Reiser 2008), an important component for accurate proactive design of industrial tasks (Chaffin, Andersson, and Martin 2006), and recent studies have focused on studying MMH tasks without foot movement constraints (Plamondon et al 2010(Plamondon et al , 2012. Although our previous studies have begun to evaluate unconstrained stepping during pickup and delivery of MMH transfers for use with predictive human figure models (Reed and Wagner 2007), the analysis from those studies was limited to the steps immediately prior to and following when the load was lifted or deposited and did not investigate any potential effects of the position of the preceding cyclic steps.…”
Section: Introductionmentioning
confidence: 99%
“…pickup or delivery tasks preceded and followed by cyclic steps). Foot placements have been identified as a critical component to accurate biomechanical evaluation of postures adopted during lifting (Authier, Lortie, and Gagnon 1996;Bendix and Eid 1983;Plamondon et al 2006;Wickel and Reiser 2008), an important component for accurate proactive design of industrial tasks (Chaffin, Andersson, and Martin 2006), and recent studies have focused on studying MMH tasks without foot movement constraints (Plamondon et al 2010(Plamondon et al , 2012. Although our previous studies have begun to evaluate unconstrained stepping during pickup and delivery of MMH transfers for use with predictive human figure models (Reed and Wagner 2007), the analysis from those studies was limited to the steps immediately prior to and following when the load was lifted or deposited and did not investigate any potential effects of the position of the preceding cyclic steps.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have examined differences between those with experience in repetitive lifting (typically within a workplace setting) and novice subjects to better understand strategies that might be useful in avoiding injury (Authier et al, 1995; Gagnon et al, 1996; Marras et al, 2006; Plamondon et al, 2010). It has been thought that these experienced lifters choose better lifting strategies, through experience, to avoid injury.…”
Section: Introductionmentioning
confidence: 99%
“…It is also thought that those with poor lifting strategies that might lead to injury would not remain in activities or occupations that required repetitive lifting due to injuries also leading to better lifting strategies in an experienced population. These studies have shown that experienced lifters exhibit different lifting strategies than novice lifters (Authier et al, 1995; Gagnon et al, 1996; Marras et al, 2006; Plamondon et al, 2010). Gagnon et al (Gagnon et al, 1996) found experienced lifters exhibited a knee flexion rather than a knee extension during the extension phase of a lifting task.…”
Section: Introductionmentioning
confidence: 99%
“…However, avoidance of increased loads or moments on the back is difficult, and the daily repetition of manual material handling may result in hyperstress on tissues of the spine, pelvis, and hip. Consequently, a strong relationship is recognized between manual material handling activities and the development of back pain 2,4) . Current recommendations emphasize the optimization of lifting techniques and ways to manually handle materials as strategies for the prevention of back pain and injuries 4) .…”
Section: Introductionmentioning
confidence: 99%
“…Manual material handling procedures are very common at industrial sites, and are one of the major factors for musculoskeletal disorders in industrial workers 2) . The mechanical properties of tissues around the lumbopelvic region (i.e., muscle length or nerve tension) affect motion of that region and contribute to low back pain 3) .…”
Section: Introductionmentioning
confidence: 99%